The Effectiveness of the by doing Model in Increasing the Learning Outcomes of Volley Ball Reservation at Sports Science Faculty - Hasibuan, Rosmaini; Siregar, Samsuddin; Bangun, Sabaruddin Yunis; Ahady, Muhammad Yan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research was conducted in line with the low competence of students in volleyball refereeing material. The purpose of this study is to improve student competence in refereeing material through the application of an experience-based by-doing model. By doing model is a learning stage that starts with simulation, observation, reflection and application. This study uses an experimental method involving two intervention groups. The sample of this research is the students of the Physical Education Study Program, Health and Recreation. The sample was divided into two groups, namely the experimental group of 15 people and the control group of 15 people. The instrument for collecting data in this study was a questionnaire with a performance test. Then each data obtained was analyzed by the technique of calculating the percentage. Based on the implementation, the results of the data analysis of this study explain that through the application of the by-doing model, it can improve student competence in volleyball refereeing material. And based on the percentage results obtained between the experimental group and the control group, it is evident that the experimental group has a higher percentage than the control group. These results explain that the application of the experience-based by doing learning model in refereeing material is better than the conventional learning model. Thus, based on the results of the study, it can be conveyed to educators that using the by-doing model is suitable to be applied in practice-based learning.